2019
DOI: 10.1002/bdm.2122
|View full text |Cite
|
Sign up to set email alerts
|

Nudges and signposts: The effect of smart defaults and pictographic risk information on retirement saving investment choices

Abstract: The authors tested two interventions to improve retirement savings investment decisions. In an incentive‐compatible experiment, 459 participants engaged in a task simulating their working life. Periodically during the simulation, participants chose between different investment options. The authors examined the effectiveness of a “nudge” by manipulating the default option and the effectiveness of a “signpost” by manipulating the display of a pictograph summarizing the expected return of each option. Participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 92 publications
(120 reference statements)
2
9
0
1
Order By: Relevance
“…In particular, we found that the expression of commonly used consumption metrics in terms of highly correlated aspects, such as environmental friendliness, increased the selection of energy efficient products. This result is in line with previous research that has pointed to the positive effects of attribute translations on decision making (Camilleri, Cam & Hoffmann, 2019;Camilleri, Larrick, et al, 2019;Ungemach et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In particular, we found that the expression of commonly used consumption metrics in terms of highly correlated aspects, such as environmental friendliness, increased the selection of energy efficient products. This result is in line with previous research that has pointed to the positive effects of attribute translations on decision making (Camilleri, Cam & Hoffmann, 2019;Camilleri, Larrick, et al, 2019;Ungemach et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, we demonstrated that the directional capacities of translations are based on an attentional prioritization process that directs pre-decisional information acquisition and integration processes towards choice options that are most congruent with the concerns and objectives highlighted by translations. This finding contributes to our understanding of attribute translations as it complements previous research, which focused primarily on the behav-ioral effects of translations on decision making (Camilleri, Cam, et al, 2019;Ungemach et al, 2018). The current study is among the first to investigate the cognitive correlates of a choice architectural intervention.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Since a choice environment is unavoidable, choice architects can organize it in a way that may change people's behavior purposefully, allowing them to decide according to what they think is right (trying to counterbalance the negative influence of our bounded rationality and the complex structure of the environment). A vegetarian default meal on a menu (Hansen et al, 2021), the default allocation of part of your salary in a retirement account (Camilleri et al, 2019), the wording in a text scheduling your vaccination explaining that it is waiting for you (Milkman et al, 2021), or a personalized email nudge to improve student homework (Smith et al, 2018) are examples of successful nudges that have influenced people's behavior increasing their wellbeing without manipulation or restricting their freedom.…”
Section: Libertarian Paternalism As a Possible Policy Path To Virtuou...mentioning
confidence: 99%
“…It has been applied to various fields as a method to influence people's behavioral decisions. Examples include influencing consumers' dietary decisions [9,10], encouraging investors to implement sustainable and responsible investment decisions [11,12], promoting students' self-directed learning educational decisions [13,14], reducing social media users' misinformation sharing decisions [15][16][17], and changing individuals' pro-social behavior decisions [18][19][20].…”
Section: Introductionmentioning
confidence: 99%